Relationship between sleep quality and mental health before and after COVID-19 epidemic among rural older adults in Shandong province - Jie LI; Shi-jun YANG; Zhi-xian LI (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo explore the relationship between sleep quality and mental health before and after the outbreak of coronavirus disease - 2019 (COVID-19) epidemic among rural older adults in Shandong province, and to provide evidence for improving sleep quality and mental health of the adults. MethodsUsing stratified multistage random sampling, 3600 rural adults aged 60 years and above were selected in three prefectures (Qufu, Laoling and Rushan), Shandong province for a baseline survey during May 2019 and a follow-up survey during August 2020. Face-to-face interviews were conducted among the adults with a self-designed questionnaire, Pittsburgh Sleep Quality Index (PSQI), and the Kessler Psychological Distress Scale (K10) to collect relevant information. The cross-lagged path analysis was used to test causal relationship between sleep quality and psychological distress before and during the COVID-19 epidemic. ResultsAmong a total of 2 749 adults completing the base line and follow-up survey, significantly increased PSQI score (9.03 ± 4.31 vs. 7.82 ± 4.52, β = 1.21) and K10 score (18.23 ± 8.06 vs. 16.64 ± 7.44, β = 1.59) during the epidemic period were observed in contrast to those 14 months ago (both P < 0.001). After adjusting for gender, age, education, marital status, annual household income per capita, smoking, alcohol drinking, self-rated health status, comorbidity of chronic diseases, and physical exercise, the results of cross-lagged path analysis showed that sleep quality before the epidemic could predict psychological distress during the epidemic (\begin{document}$ρ _1 $\end{document} = 0.041, P = 0.015), but psychological distress before the epidemic could not predict sleep quality during the epidemic (\begin{document}$ρ _2 $\end{document} = − 0.005, P = 0.749), with a significant disparity in the difference between the values of the two coefficients (\begin{document}$ρ _1 $\end{document} > \begin{document}$ρ _2 $\end{document}, P < 0.001), which suggested that there was a one-way causal temporal relationship between sleep quality and psychological distress.ConclusionThe sleep quality and mental health status of rural older adults in Shandong province were worsen after the outbreak of the COVID-19 epidemic and the older adults with poor sleep quality are more likely to have psychological distress.